Does intangible asset intensity increase profit-shifting opportunities of multinationals? - Roberto Crotti (Graduate Institute of International and Development Studies, 2021)
This paper studies how intangible asset intensity affects multinationals' profitshifting behavior. Intangible assets reduce the cost of booking profits in low-tax jurisdictions, independently from where profits are generated. Consequently they can be instrumental to implementing tax-avoidance schemes. Using a large firm-level, parent-subsidiaries matched panel data set I test if multinationals characterized by high intangible asset intensity report higher profits in low-tax jurisdictions, respect to corporations with low intangible asset intensity. I find that, intangible asset intensity exacerbates multinationals' profit-shifting behavior. Splitting the sample between tech and non-tech companies, I find that, although tech companies leverage intangible asset intensity for profit-shifting more than the rest of the sample, there is no statistical difference between profit-shifting of tech companies with high intangibles intensity and non-tech companies with high intangibles intensity.
Keywords: F23; H25; 330; intangible assets; international profit-shifting; corporate taxation